Digestibilidade de fontes proteicas e disponibilidade de fosfatos inorgânicos em três fases de desenvolvimento da tilápia-do-nilo - Pinto, Luis Gabriel Quintero; Pezzato, Luiz Edivaldo [UNESP]; Gamboa, Blanca Stella Pardo; Araujo, Daniel de Magalhães (Boletim do Instituto de Pesca, 2017)
Apparent digestibility of nutrients in several protein ingredients and inorganic phosphates were compared in three Nile tilapia different development stage. The ingredients tested were fish meal, chicken by-product meal, meat and bone meal, corn gluten, soybean meal, cotton seed meal, mono-bi-calcium phosphate, bi-calcium phosphate, mono-potassium phosphate and phosphoric acid. The apparent digestibility coefficients of dry matter, crude protein, gross energy, phosphorus, calcium and magnesium were determined with 25g, 250g and 500g fish. It was concluded that, the capacity of Nile tilapia to digesting feed and absorbing nutrients is dependent on the body weight and characteristics of food evaluated. There was a trend to better utilization of nutrients from animal origin foods and inorganic sources by 25g fish. The fishes with 250g and 500g showed better use of plant protein sources than 25g fish.
Protein sources digestibility and inorganic phosphates availability by Nile tilapia in tree development stages
Keywords: Development stages; Digestible nutrients; Mineral supplements; Oreochromis niloticus; Phosphorus available; Protein ingredients